1988
DOI: 10.1002/ejsp.2420180206
|View full text |Cite
|
Sign up to set email alerts
|

‘Numerical trap’. A new look at outcome representation in studies on choice behaviour

Abstract: In almost all experimental studies on choice behaviour the consequences of choices are limited to denumerable goods (usually money)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Past research has shown how outcome representation or the coding of prospective outcomes as gains or as losses relative to a salient anchor point influence concession making and integrative agreements (e.g. Bazerman, Magliozzi, & Neale, 1985;De Dreu, Carnevale, Emans, & Van de Vliert, 1994;Grzelak, 1986;Grzelak, Poppe, Czwartosz, & Nowak, 1988). Current findings show that also the content of the issues at the negotiation table are of great importance, and affect negotiation processes and outcomes in predictable ways.…”
Section: Contribution To Theorymentioning
confidence: 62%
“…Past research has shown how outcome representation or the coding of prospective outcomes as gains or as losses relative to a salient anchor point influence concession making and integrative agreements (e.g. Bazerman, Magliozzi, & Neale, 1985;De Dreu, Carnevale, Emans, & Van de Vliert, 1994;Grzelak, 1986;Grzelak, Poppe, Czwartosz, & Nowak, 1988). Current findings show that also the content of the issues at the negotiation table are of great importance, and affect negotiation processes and outcomes in predictable ways.…”
Section: Contribution To Theorymentioning
confidence: 62%
“…With only a few exceptions (e.g. Grzelak, 1982Grzelak, , 1986Grzelak et al, 1988Grzelak et al, , 1989 they were assessed by having people allocate money or points (which usually refered to money) to themselves and/or one other person who was in a similar situation as the allocator. However, in the present study, these restrictions were removed.…”
Section: Discussionmentioning
confidence: 99%
“…For each participant, Spearman rank-order correlations (with corrections for ties) were computed between the participant's rank order and the perfect rank orders in Table 1 and Table 2 (Wieczorkowska, 1982;Grzelak et al, 1988). Each correlation was transformed into a Fisher-z coefficient.…”
Section: Computation Of the Dependent Variablesmentioning
confidence: 99%
“…Grzelak, Poppe, Czwartosz, & Nowak (1988) report that cooperative and altruistic motives are more strongly activated when own and other's satisfaction with money are represented iconically (i.e. smiling versus frowning faces) than when represented geometrically (i.e.…”
Section: Representation Of Resources To Be Distributedmentioning
confidence: 96%